Synthesis of Hydrosiapatite from Muscle Shell Waste Using The Precipitation Method - Puspitawati, Ika Nawang; Tauhid, Aziz Hafizh; M.N.K, Abdullah Tsani; Utami, Lucky Indrati; Wahyusi, Kindriari Nurma (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
Hydroxyapatite is a calcium phosphate compound that is the main inorganic component of bones and teeth. Hydroxyapatite has a main role in the medical world because of its identical chemical properties and structure to human bone. Kupang shells have a high CaCO3 content of 95-99% by weight. So this concurrence, the mussel shells are to be used as good as an ingredient for making Hydroxyapatite. The variables used in this research are Temperature of the Furnace and Phosphoric Acid Concentration, which were 700ºC, 750 ºC, 800 ºC, 850 ºC, 900 ºC and Phosphate Acid Concentrations 0.4M, 0.6M, 0.8M, 1M, and 1.2M. The product results were tested with XRD analysis to determine the crystal structure contained in the product and the level of Hydroxyapatite in the product. The best research results in this study at a temperature of 900ºC at a concentration of 1.2M phosphoric acid with a Hydroxyapatite content of 100% with lattice parameters an (Aº)=b (Aº) = 9..422, c (Aº)=6.8835, and gamma = 120º.